RESEARCH OF PROPERTIES OF THE NANOMODIFIED COVERAGES, ON BASIS OF THE FLUOROPLASTICS F-30 P - OLEKSANDRENKO, VICTOR; SVIDERSRKYI, VLADYSLAV; KIRICHENKO, LUDMILA; DANILENKO, IHOR; YEFYMENKO, VALERIJ; NELYUBIN, YURII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Ways to enhance the physical and mechanical properties and wear resistance of fluoroplastic coatings on metal surfaces were analyzed. The influence of composition and temperature-time conditions of forming multilayer fluoroplastic coatings on their abrasion resistance, microhardness, and corrosion resistance were studied. Technological operation modes were described, and the properties of developed coatings based on fluoropolymer F-30P were presented. The research on the wear resistance of developed fluoroplastic coatings has shown that the addition of 17 wt.% graphite С-1 and 1 wt.% aminoorganosilicon based on Aerosil, as well as 2 wt.% ZrO2 + 3% Y2O3 (500 °C) or 2 wt.% ZrO2 + 3% Y2O3 (700 °C) or 2 wt.% amorphous zirconium hydroxide doped with yttrium ions (the amount of yttrium in terms of oxides is 3 mol%) to the external layer of the three-layer fluoroplastic coating based on F-30 П results in an increase in the abrasion resistance of the coating by 1.38, 1.57, and 1.83 times, respectively. The lowest microhardness of the three-layer fluoroplastic coating, which includes the outer layer composed of F-30P fluoropolymer + 17 wt. % C-1 graphite + 1 wt. % aminoorgano silicon based on Aerosil + 2 wt. % amorphous zirconium hydroxide alloyed with yttrium ions (the amount of yttrium in terms of oxides is 3 mol %), compared to fluoroplastic coatings modified with nanopowders of zirconium oxides, can be explained by the amorphous structure of the nanomodifier. It has been established that the coating with the nanomodifier Zr(Y)O(OH)2 possessing the best corrosion resistance parameters. A technology has been developed for the pre-treatment and electrostatic application of a nanomodified fluoroplastic coating on a metal surface: it requires the mandatory drying of compressed air, the selection of an optimal distance between electrodes, and the first priming layer should be applied at an electrostatic field intensity of 50 kV, while the intensity should be increased to 70 kV for subsequent layers.
Keywords: adhesion; fluoroplastic coatings; strength; composition; technological factors; metal surface; microhardness; and corrosion resistance were studied; anti-abrasion